JWST Constraints on the UV Luminosity Density at Cosmic Dawn: Implications for 21 cm Cosmology - Sultan Hassan; Christopher C. Lovell; Piero Madau; Marc Huertas-Company; Rachel S. Somerville; Blakesley Burkhart; Keri L. Dixon; Robert Feldmann; Tjitske K. Starkenburg; John F. Wu; Christian Kragh Jespersen; Joseph D. Gelfand; et al. (The Astrophysical Journal Letters, 2023)
An unprecedented array of new observational capabilities are starting to yield key constraints on models of the epoch of first light in the Universe. In this Letter we discuss the implications of the UV radiation background at cosmic dawn inferred by recent JWST observations for radio experiments aimed at detecting the redshifted 21 cm hyperfine transition of diffuse neutral hydrogen. Under the basic assumption that the 21 cm signal is activated by the Ly α photon field produced by metal-poor stellar systems, we show that a detection at the low frequencies of the EDGES and SARAS3 experiments may be expected from a simple extrapolation of the declining UV luminosity density inferred at z ≲ 14 from JWST early galaxy data. Accounting for an early radiation excess above the cosmic microwave background suggests a shallower or flat evolution to simultaneously reproduce low- and high- z current UV luminosity density constraints, which cannot be entirely ruled out, given the large uncertainties from cosmic variance and the faint-end slope of the galaxy luminosity function at cosmic dawn. Our findings raise the intriguing possibility that a high star formation efficiency at early times may trigger the onset of intense Ly α emission at redshift z ≲ 20 and produce a cosmic 21 cm absorption signal 200 Myr after the Big Bang.